Effectiveness and safety of ear acupuncture for allergic rhinitis: A protocol of randomized controlled trial. Issue 12 (26th March 2021) - Ding, Xiaojun; Huang, Shufen; Tang, Yajun; Lin, Jia
Abstract: Background: Allergic rhinitis is a global problem. About 10% to 40% of the global population is affected by allergic rhinitis and is on the rise, which has a significant health and economic impact on society. Ear acupuncture is a non-invasive acupuncture therapy, which has been used in the treatment of allergic rhinitis, and some positive results have been reported, but there is not enough evidence to prove its efficacy and safety. Methods: This is a single-center, randomized, single-blind, sham-controlled trial. With the approval of the ethics committee of our hospital, participants with allergic rhinitis will be randomly assigned to receive either real or sham ear acupuncture once a week for 8 weeks, followed by 12 weeks of follow-up. Evaluate the patient's nasal symptom score and Standardised Rhinoconjunctivitis Quality of Life Questionnaire score, and monitor adverse events. Finally, the data are analyzed by SPSS 22.0 software. Discussion: The results of this study will determine the efficacy and safety of ear acupuncture in the treatment of allergic rhinitis and provide a basis for promoting the application of ear acupuncture in the treatment of allergic rhinitis. Trial registration: OSF Registration number: DOI 10.17605/OSF.IO/MVEF7.